Students’ Reflection towards the Integration of Tawhidic Science in the “Pandang Alam” Camp - Iksan, Zanaton H; Basri, Nurasika Andi; Md Noor, Nurul Jannah; Rahim, Faszly; Wan Abdullah, Wan Nasyrudin; Rambely, Azmin Sham; Wan Ahmad, Wan Juliana; Hazmi, Izfa Riza; Hanifah, Sharina Abu (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The purpose of this study is to observe students’ reflection towards the integration of Tawhidic Science at the program “Kem Pandang Alam”, at Tanjung Tuan Wildlife Reserve and several other locations nearby Tanjung Tuan, Teluk Kemang and Si Rusa, Port Dickson, Negeri Sembilan Malaysia. The respondents of this study were 32 students from tahfiz schools and tahfiz science schools (15 boys and 17 girls). These students were exclusively selected candidates from their respective schools. Data were analysed based on constant comparative analysis. The finding reveals that there were seven themes including greatness of God’s knowledge; nature as the source of knowledge, education and lesson; improvement of faith; self-development, the formation of identity, the increase of awareness, and the closer of social relations. The implication of this study is to expose these students the importance of the integration of Tawhidic Science where science and religion are inseparable from everyday life.